High Serum Level of TNF-α in Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis - Huyen, Tran Thi; Lan, Pham Thi (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis are severe cutaneous adverse drug reactions. Some immunological and genetic factors are believed to be involved in the pathogenesis of SJS/TEN, including tumor necrotic factor-alpha (TNF-α). Activated T-cells secrete high amounts of TNF-α and interferon-gamma that both cytokines lead to increased expression and activity of keratinocyte inducible nitric oxide synthase playing an important role in the apoptosis of keratinocytes. AIM: This study aims to evaluate the serum level of TNF-α in SJS/TEN and the relation between it and the progress of SJS/TEN. METHODS: This was a sectional descriptive study conducted at the National Hospital of Dermatology and Venereology, in Hanoi, Vietnam, from October 2017 to September 2019. Forty-eight SJS/TEN patients, 43 erythema multiforme (EM) patients, and 20 healthy controls (HCs) participated. TNF-α levels were measured using the fluorescence covalent microbead immunosorbent assay (FCMIA) (ProcartaPlex Immunoassay Panels kit, Thermo Fisher Scientific, USA). The Mann–Whitney U-test was used to compare serum TNF-α levels of two groups. The Wilcoxon tests were used to compare quantitative variables before and after the treatment. Differences were considered to be statistically significant at p < 0.05. RESULTS: Nineteen SJS patients (39.5%) and 29 TEN patients (60.5%) participated in our study. The mean age was 49.3, range 19−77 years (47.9% of males and 52.1% of females). The most common causative drugs were traditional medicine (29.1%), carbamazepine (12.5%), and allopurinol (12.5%). On the day of hospitalization, the mean serum level of the SJS/TEN group was 32.6 pg/ml with a range from 1.3 pg/ml to 771.2 pg/ml. This level was significantly higher than that of the HCs group (p < 0.05) but not higher than that of the EM group. The mean serum level of TNF-α in the SJS/TEN patients on the day of hospitalization was 32.6 pg/ml, higher than that on the day of re-epithelialization (2.7 pg/ml) and the difference was statistically significant with p < 0.05. CONCLUSION: Serum TNF-α levels are a good biomarker to evaluate the progress of SJS/TEN but it is not good to differentiate SJS/TEN from EM.